PARTNERSHIP SCHEME IMPLEMENTATION AND BUSINESS SUCCESS IN BROILER FARMING: AN EMPIRICAL ANALYSIS - WIDIARTA, I PUTU GEDE DIDIK; Qamara, Cori; Agung, Ananda Putra; Aldiyanti, Amani (Jurnal Ilmu Ternak Universitas Padjadjaran, 2025)
The partnership scheme in broiler farming aims to enhance farmers' productivity and profitability through technical support, market access, and the provision of production inputs. However, variations in its implementation effectiveness significantly impact farmers' business success. This study examines the relationship between the level of partnership scheme implementation and the success of broiler farming businesses in Kutai Kartanegara Regency, East Kalimantan. A quantitative approach was employed, using structured questionnaires to collect data from 220 farmers selected through purposive sampling. Data were analyzed using descriptive statistics, Pearson correlation, and multiple linear regression to identify key factors influencing business success, including feed management, breed quality, animal health, and technical assistance. The findings indicate that the implementation of partnership schemes has a positive and significant relationship with broiler farming success, with feed management (β = 0.45, p < 0.01) and breed quality (β = 0.39, p < 0.05) being the most influential factors. However, challenges such as fluctuating feed costs, limited access to technology, and uneven technical support hinder the optimal application of partnership schemes. Therefore, improving infrastructure, expanding access to technology, and developing cost-stabilization strategies are essential to enhancing the effectiveness of partnership schemes and ensuring the long-term sustainability of broiler farming businesses.